Pelatihan Pembuatan Alat Pembasmi Hama Modern Berbasis Solar Cell Pada Petani Bawang Merah - prasetya, kartika; Elsanda Merita Indrawati; M. Dewi Manikta Puspitasari; Miftakhul Maulidina; Fanny Anggoro (Universitas Nusantara PGRI Kediri, 2021)
Abstract— Shallots are one of the spices that have unstable prices where the price of shallots can be high but in a short time the price of shallots can drop down, many factors cause instability in the price of shallots in the market, one of which is the main factor in crop failure caused by pest attack. The main pest of shallot farmers is in the form of leafhoppers, the effort to control leafhoppers is the use of pesticides. However, this method is less than optimal because it requires a lot of money, excessive use of pesticides causes environmental damage. Based on these problems, the researchers designed a pest control device in the form of a modern, environmentally friendly pest control device based on solar cells. This service activity includes observation, analysis, training, monitoring and evaluation. The final results of this PKM activity are: 1) improving the skills of farmers so that they can design modern and environmentally friendly pest control tools for shallot plants; 2) a solar cell-based pest control device can work effectively in eradicating where in 1 night on average the tool can kill planthoppers, bugs, grasshoppers and kaper as much as 1/2 kg.